Study on Galanthus species in the Bulgarian flora - Ivanka Semerdjieva; Boryana Sidjimova; Elina Yankova-Tsvetkova; Milena Kostova; Valtcho D. Zheljazkov (Heliyon, 2019)
Genus Galanthus (Amaryllidaceae) includes 19 species in Europe and the Middle East. The Flora of Bulgaria recognizes two species: G. nivalis L. and G. elwesii Hook. Galanthus elwesii is characterized by relatively high morphological variability, leading some authors to identify some populations as G. gracilis Celak. However, the occurrence of G. gracilis in the Bulgarian flora is disputed. The hypothesis was that populations previously identified as G. gracilis belong indeed to a separate species. Therefore, the objective of this study was to compare G. nivalis and G. elwesii with plants from populations previously identified as G. gracilis. Morphological, DNA, embryological and anatomical analyzes were conducted to meet the objective. The morphological characteristics and DNA dendrogram revealed that G. gracilis and G. elwesii were situated in the same cluster and had significant morphological similarity, whereas plants from populations identified as G. nivalis were dissimilar in morphology and situated in a separate cluster. The revealed features of the generative sphere showed similarities across the species. Scanning electron microscopy (SEM) analyses of the surface revealed that the anticillinal walls of G. elwesii and G. gracilis were straight, while those of G. nivalis were wavy. This research demonstrated that the plants of G. elwesii and those from populations identified as G. gracilis are morphologically, embryologically and genetically similar, thus refuting the hypothesis. This study did not provide sufficient evidence to support the claim of the existence of G. gracilis in the Bulgarian flora; the populations identified as G. gracilis in Bulgaria may be forms of G. elwesii.